Degradation of cellulosic material by cellulomonas fimi - Kane, Steven Daniel (The University of Edinburgh, 2015)
The world stocks of fossil fuels are dwindling and may be all but out before the end of the century. Despite this there is increasing demand for them to be used for transport, and the ever increasing green house gases which their use produces. Renewable and less environmentally damaging forms of fuel are needed. Biofuels, particularly bioethanol, are a possibility to subsidise or replace fossil fuels altogether. Ethanol produced from fermentation of starch sugars from corn are already in wide use. As this bioethanol is currently produced from crops such as corn and sugar cane, that puts fuel crops in direct competition for space and resources with food crops. This has led to increases in food prices and the search for more arable land. Hydrolysis of lignocellulosic biomass, a waste by-product of many industries, to produce the sugars necessary for ethanol production would ease many of the problems with current biofuels. Degradation of lignocellulose is not simple and requires expensive chemical pre-treatments and large quantities of enzymes usually from fungal species making it about 10 times more expensive to produce than corn starch bioethanol. The production of a consolidated bioprocessor, an organism able to degrade, metabolise and ferment cellulosic material to produce ethanol or other useful products would greatly reduce the cost currently associated with lignocellulosic biofuel. Cellulomonas fimi ATCC 484 is an actinomycete soil bacterium able to degrade efficiently cellulosic material. The US Department of Energy (DOE) released the genome sequence at the start of 2012. In this thesis the released genome has been searched, for genes annotated as encoding polysaccharide degrading enzymes as well as for metabolic pathways. Over 100 genes predicted to code for polysaccharide hydrolysing enzymes were identified. Fifteen of these genes have been cloned as BioBricks, the standard synthetic biology functional unit, expressed in E. coli and C. freundii and assayed for endo β-1,4-glucanase activity using RBB-CMC, endo β-1,4-xylanase activity using RBB-xylan, β-D-xylosidase activity using ONPX, β-D-cellobiohydrolase activity using ONPC and α-L-arabinofuranosidase activity using PNPA. Eleven enzymes not previously reported from C. fimi were identified as active on a substrate with the strongest activities being for 2 arabinofuranosidases (AfsA+B), 4 β-xylosidases (BxyC, BxyF, CelE and XynH), an endoglucanase (CelA), and 2 multifunctional enzymes CelD and XynF, active as cellobiohydrolases, xylosidases and endoxylanases. Four enzymes were purified from E. coli cell lysates and characterised. It was found that AfsB has an optimum activity at pH 6.5 and 45ºC, BxyF has optimum activity at pH 6.0 and 45ºC and XynH has optimum activity at pH 9.0 and 80ºC. XynF exhibited different optima for the 3 substrates with pH 6.0 and 60ºC for ONPC, pH 4.5 and 50ºC for ONPX and pH 5.5 and 40ºC for RBB-xylan. Searching the genome and screening genes for activities will help genome annotation in the future by increasing the number of positively annotated genes in the databases. The BioBrick format is well suited for rapid cloning and expression of genes to be classified. Searching and screening the genome has also given insights into the complex and large network of enzymes required to fully hydrolyse and metabolise the sugars released from lignocellulose. These enzymes are spread across many different glycosyl hydrolase families conferring different catalytic activities. The characterisation of these novel enzymes points towards a system adapted to not only a broad specificity of substrate but also environmental factors such as high temperature and pH. Genomic analysis revealed gene clusters and traits which could be used in the design of a synthetic cellulolytic network, or for the conversion of C. fimi into a consolidated bioprocessor itself.
Keywords: cellulomonas fimi; cellulose hydrolysis; arabinofuranosidase; β-xylosidase; xylanase; thermo-optimal; alkaline optimal; genome